2008
DOI: 10.1182/blood.v112.11.158.158
|View full text |Cite
|
Sign up to set email alerts
|

Superior Complete Response Rate and Progression-Free Survival after Autologous Transplantation with up-Front Velcade-Thalidomide- Dexamethasone Compared with Thalidomide-Dexamethasone in Newly Diagnosed Multiple Myeloma

Abstract: Over the last few years, Thalidomide-Dexamethsone (TD) has been one of the most commonly used induction regimens for the treatment of newly diagnosed multiple myeloma (MM). In a phase III study conducted by the Italian Myeloma Network GIMEMA, TD was compared with Velcade-Thalidomide-Dexamethasone (VTD) as induction therapy in preparation for, and as consolidation after, melphalan (200 mg/m2)-based double autologous stem-cell transplantation (ASCT) in pts aged ≤65 years with symptomatic MM. Up-front VTD compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 0 publications
3
32
0
Order By: Relevance
“…This group was also able to demonstrate that bortezomib maintenance was well tolerated and induced additional response. Similar to the report by Cavo et al (2008), bortezomib treatment overcame poor risk caused by renal dysfunction and adverse cytogenetics, together with a beneficial effect on other adverse features associated with poor risk, including t(4;14) and 17p del. Interestingly, additional responses were also achieved with thalidomide maintenance in the conventional arm and improving outcome, pointing to the pivotal role novel therapies provide.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…This group was also able to demonstrate that bortezomib maintenance was well tolerated and induced additional response. Similar to the report by Cavo et al (2008), bortezomib treatment overcame poor risk caused by renal dysfunction and adverse cytogenetics, together with a beneficial effect on other adverse features associated with poor risk, including t(4;14) and 17p del. Interestingly, additional responses were also achieved with thalidomide maintenance in the conventional arm and improving outcome, pointing to the pivotal role novel therapies provide.…”
supporting
confidence: 70%
“…A study from the IFM group led by Harousseau and colleagues demonstrated that lower dose bortezomib with thalidomide and dexamethasone (vTD) was better tolerated and quite active (as opposed to higher dose bortezomib and dexamethasone alone), although the reduced dose of bortezomib may result in a lower rate of high quality of response. Similarly, Rosiñol and colleagues demonstrated convincingly that, again, the three‐drug combination of VTD was superior to both TD and combination chemotherapy with bortezomib alone (but without IMiD‐based therapy) (Cavo et al , 2008, 2010; Rosiñol et al , 2008, 2009; Harousseau et al , 2009; Moreau et al , 2010). Overall, VTD results in improved responses to induction therapy and improved responses to protocol‐directed treatment, including SCT, and (despite increased peripheral neuropathy) is associated with generally manageable side effects.…”
mentioning
confidence: 93%
“…survival (PFS) compared with older induction regimens (Cavo et al, 2008;Harousseau et al, 2008). For patients who are not candidates for HDT-SCT, combinations of new and old drugs offer improved response rates, PFS and overall survival (OS) (Facon et al, 2007;San Miguel et al, 2008).…”
mentioning
confidence: 99%
“…Both regimens were active as frontline induction, with lower toxicity after PAD2. Results from a GIMEMA trial comparing Bor-Thal-Dex with Thal+ Dex induction and consolidation therapy following double ASCT with Mel 200 mg ⁄ m 2 indicate that Bor-Thal-Dex resulted in a higher ‡ PR rate after induction (33% CR+nCR, 61% ‡ VGPR vs. 12% CR+nCR, 30% ‡ VGPR) and after the first transplantation (54% CR+nCR, 75% ‡ VGPR vs. 29% CR+nCR, 53% ‡ VGPR), which was associated with significantly higher 2-yr PFS (90% vs. 80%; P < 0.001; Table 2) (47). In a phase I ⁄ II study in newly diagnosed patients, the combination Bor-Len-Dex resulted in a PR rate of 98%, including 71% ‡ VGPR and 29% CR+nCR.…”
Section: New Drugs Combined With Chemotherapeutic Agents As Inductionmentioning
confidence: 98%
“…Key studies investigating the use of novel chemotherapies as induction therapy before autologous stem-cell transplantation Dex, dexamethasone; Doxo, doxorubicin; HDT, high-dose therapy; HR, hazard ratio; NA, not available; NS, not significant; OS, overall survival; PLD, pegylated liposomal doxorubicin; PFS, progression-free survival; Thal, thalidomide.Palumbo and Rajkumar have been tested in combination with Dex and other chemotherapeutic agents as induction treatment in newly diagnosed patients(Table 2)(43)(44)(45)(46)(47)(48).…”
mentioning
confidence: 99%